2013
DOI: 10.6116/kjh.2013.28.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Hovenia dulcis Extract on Acute and Chronic Liver Injuries induced by Alcohol and Carbon Tetrachloride

Abstract: Objectives : The purpose of this study was to evaluate the hepatoprotective effect of Hovenia dulcis extract on acute and chronic liver injuries induced by alcohol and CCl4 in mice and rats.Methods : In acute alcohol-induced liver injury, mice were administered Hovenia dulcis extracts (60 and 200 mg/kg) orally before and after alcohol administration. In chronic alcohol-induced liver injury, mice were administered alcohol containing liquid diet for 4 weeks. The mice were administered H. dulcis extracts (60 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Several in vivo studies have been conducted to evaluate the hepatoprotective effect of H. Dulcis extract in various models of liver injuries induced by chemicals toxins [ 14 , 59 , 60 ].…”
Section: Pharmacological Activities Of H Dulcis mentioning
confidence: 99%
“…Several in vivo studies have been conducted to evaluate the hepatoprotective effect of H. Dulcis extract in various models of liver injuries induced by chemicals toxins [ 14 , 59 , 60 ].…”
Section: Pharmacological Activities Of H Dulcis mentioning
confidence: 99%
“…NMED-01군에서 혈중 γ -GTP가 유의하게 낮아진 결과는 알코올로 인하여 손상된 간세포가 수복되었다는 것을 의미한 다. 이는 알코올로 유발한 만성 간손상 모델에서 NMED-01 을 먹은 흰쥐가 AST, ALT 증가가 억제되었다는 동물실험 결 과 46…”
Section: 간기능 수치 변화unclassified
“…枳椇子 에탄올추출물은 사염화탄소(CCl4) 또 는 알코올 유도 급성 간손상 동물모델에서 혈청의 AST, ALT 증가를 억제하고 [26][27][28] , MDA, hydroxyproline 증가를 억제함 이 보고되어 있다 27,29) . 枳椇子 열수추출물은 CCl4 또는 D-galactosamine/LPS 유도 간손상 모델에서 혈장 내 AST, ALT, LDH, ALP 수준을 감소시키며 6,12,24) , 알코올 유도 간손 상 동물모델에서도 혈중 알코올 농도를 저하시키고 혈장 내 AST 수준을 감소시켜 간보호 효과를 나타냄이 보고되었다 6,46) . 葛根 열수추출물은 사염화탄소 유도 급성 간손상 동물모델 에서 AST, ALP를 유의하게 감소시키고 39,47) 에탄올 유도 간 손상 동물모델에서도 ALT, AST를 유의하게 감소시켰다 48) .…”
unclassified
“…In vitro and in vivo studies have demonstrated the hepatoprotective [3,9] and anti-adipogenic [5] activities of the crude extracts of H. duclis. Kim et al [10] illustrated that H. duclis extracts significantly prevented alcohol-induced acute and chronic liver injury in mice. The extract also reduced the carbon tetrachloride (CCl 4 )-induced rise in the plasma levels of liver enzymes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10] illustrated that H. duclis extracts significantly prevented alcohol-induced acute and chronic liver injury in mice. The extract also reduced the carbon tetrachloride (CCl 4 )-induced rise in the plasma levels of liver enzymes [10,11].…”
Section: Introductionmentioning
confidence: 99%